Relación entre economía circular y el turismo de naturaleza - Hugo Alberto Martínez Jaramillo; Yolanda González Castro; Omaira Manzano Durán (Mundo Fesc)
To talk about the circular economy is to mention topics such as sustainability, waste minimization, and, in the long term, economic development. This research used a qualitative paradigm based on a documentary review to identify the relationship between nature tourism and the circular economy using scientific databases. The Scopus database was used for the quality of its editorial processes, and VOSviewer software was used to visualize bibliometric networks. Three clusters were identified with research trends: Circular Economy for Development, Responsible Tourism, and Sustainable Challenges. The first cluster demonstrates a direct relationship between the circular economy, profitability, and job creation. The second cluster demonstrates the need for social awareness in the tourism sector as a factor of responsibility toward both internal and external customers. The third cluster highlights the challenges of this association and how to contribute to Sustainable Development Goal 1, the goal of ending poverty, in addition to the need to implement digital transformation in new business models.